2023
DOI: 10.3390/pharmaceutics15122780
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Titanate Nanotubes with a Carboxylic Arm for Further Functionalization Intended to Pharmaceutical Applications

Ranim Saker,
Orsolya Jójárt-Laczkovich,
Géza Regdon
et al.

Abstract: Nanotechnology is playing a significant role in modern life with tremendous potential and promising results in almost every domain, especially the pharmaceutical one. The impressive performance of nanomaterials is shaping the future of science and revolutionizing the traditional concepts of industry and research. Titanate nanotubes (TNTs) are one of these novel entities that became an appropriate choice to apply in several platforms due to their remarkable properties such as preparation simplicity, high stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As TNTs have promising potential to be used in multiple applications, their fragile structure should be taken into consideration, as it could undergo numerous changes during handling/processing. For example, TNTs could be easily broken up due to mechanical forces such as stirring or ultrasonication, resulting in shorter nanotubes [10,37]. Also, extremely high-temperature treatments used in many procedures could result in changing the surface chemistry and reducing the number of OH groups on it.…”
Section: Stability Of the Prepared Nanotubesmentioning
confidence: 99%
See 4 more Smart Citations
“…As TNTs have promising potential to be used in multiple applications, their fragile structure should be taken into consideration, as it could undergo numerous changes during handling/processing. For example, TNTs could be easily broken up due to mechanical forces such as stirring or ultrasonication, resulting in shorter nanotubes [10,37]. Also, extremely high-temperature treatments used in many procedures could result in changing the surface chemistry and reducing the number of OH groups on it.…”
Section: Stability Of the Prepared Nanotubesmentioning
confidence: 99%
“…Furthermore, their safety/toxicity studies still present conflicting results. Some studies have reported their safe use without showing any toxic effects [7,10,80]. Others even displayed positive outcomes such as increased cell viability [8], enhanced proliferation, and bone cell adhesion [81], probably due to their porous structure allowing the flow of nutrients and blood [82], while other studies reported their toxic effects and classified them as more toxic than other nanomaterials such as nanorods, nanoribbons, and nanowires [83,84].…”
Section: Applications In the Pharmaceutical Fieldmentioning
confidence: 99%
See 3 more Smart Citations